Magnetic resonance imaging findings in dogs with orbital inflammation. (2nd October 2018) - Fischer, M. C.; Busse, C.; Adrian, A. M.
Abstract : Objectives: To describe MRI features of canine retrobulbar inflammation, their association with clinical findings and outcome and to assess the value of MRI in detecting orbital foreign bodies. Materials and Methods: Clinical records of dogs with confirmed (23 of 31) and suspected (eight of 31) retrobulbar inflammation that underwent low field MRI studies were analysed retrospectively. Results: Of the 31 dogs included in the study there was abscessation in 19. Extraocular myositis (27 of 31) was concurrent with strabismus in three cases. Of 25 patients with exophthalmos, 14 had concurrent optic nerve swelling and, of these, five had permanent loss of vision. There was no vision loss in patients without nerve swelling. One case of suspected retinal detachment on MRI was confirmed clinically. Extensive abnormal contrast enhancement in the temporalis, masseter and pterygoideus muscles was associated with facial (n=3) and trigeminal nerve deficits (n=1). Three patients with inflammation extending into the nasal cavity and frontal sinus (one of 31) or meningeal contrast enhancement (two of 31), showed optic and oculomotor nerve deficits. On MRI a foreign body was not visible in 20 of 31 case or "appeared likely" in 11 of 31 dogs. A foreign body was found at surgery in one case. Clinical Significance: MRI outlines the extent of retrobulbar inflammation. Clinical findings were associated with imaging findings. MRI overestimated the presence of foreign bodies.